Evaluation of Textbook: Analyzing English Book II at Intermediate Level of KP Textbook Board in the Light of Bloom’s Taxonomy of Educational Objectives - Dr.Humaira Jabeen; Syeda Neelam; Dr. Ahmad Sohail Lodhi (Dialogue Social Science Review (DSSR), 2025)
The textbook is a key component in most language programs. In an English language as a foreign language context, it may even establish the main and perhaps only source of language input that learners receive for the language practice that occurs both inside and outside of the classroom, basically in Pakistan. However, research has suggested that despite the important role of the textbook, they are not always professionally designed and do not always fit the curriculum and closely correspond with the aims of the teaching program and the needs of the students. The study aimed to evaluate the Intermediate English textbook for 12th-grade students published by the Khyber Pakhtunkhwa Textbook Board in Pakistan using Bloom's Taxonomy of Educational Objectives. The examination is systematic in nature, which centers on the subject of the exploration to see the similarity of the substance and activities of the book against the different areas and sub-classes of the Bloom's Taxonomy. The research produces a range of implementable conclusions for further study. Thus, textbooks should be carefully assessed and selected before being used for a language program. Overemphasis on cognitive skills may result in learners being able to recall and explain concepts but struggling with applying them in real-world or practical scenarios. The textbook might fail to engage students emotionally or fail to adoptive attitudes and values, which are critical for subjects like ethics, teamwork, or professional responsibility. It was also concluded that the textbook focused on written communication skills more than the oral communication skills of the learners. Textbook’s evaluation helps the managerial and teaching staff in selecting the most appropriate materials available for a particular course. It also helps to identify the strengths and weaknesses of a particular textbook that is already in use. This also helps in informing teachers in the process of textbook’s revision and decision-making for the next course.